KEMAMPUAN ARGUMENTASI ILMIAH MAHASISWA BIOLOGI ISDIK KIE RAHA MALUKU UTARA - Taher, Taufiq; Ermin, Ermin; Kasman, Rifai; Hidayat, Muhammad; B. Ali, Muhammad Iksan; Andres, Jena; Marsaoly, Najamudin (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
This study aims to analyze the scientific argumentation skills of Biology students at ISDIK Kie Raha across different academic semesters. Four semester groups (1, 3, 5, and 7) were assessed using seven indicators of argumentation: logical reasoning, data analysis, conclusion development, digital literacy, critical thinking, use of evidence, and oral argumentation. Data were collected through observation sheets and analyzed using descriptive statistics, one-way ANOVA, and Tukey HSD post hoc tests. The results indicate a significant increase in argumentation skills with higher semesters (p < 0.05). First-semester students demonstrated basic argumentation abilities, while third-semester students showed moderate improvement. Substantial gains were observed in the fifth semester, particularly in data analysis and evidence use. Seventh-semester students achieved the highest scores across most indicators, reflecting more advanced, coherent, and evidence-based scientific argumentation. These improvements were influenced by academic experience, laboratory activities, research engagement, and scientific discussions. The study concludes that the curriculum effectively supports the development of students’ argumentation skills; however, strengthening argumentation-based learning is necessary at earlier semesters to ensure more consistent progression. The findings provide important implications for the implementation of evidence-oriented and inquiry-driven instructional strategies in higher education.